Critical current degradation behavior of 7-filamentary Ba1−xKxFe2As2 tapes under uniaxial strain. (1st January 2023) - Liu, Xiao; Shi, Yi; Liu, Fang; Ma, Hongjun; Liu, Huajun; Zhou, Chao; Song, Yuntao; Gao, Jian; Zhu, Yanchang; Zhang, Xianping; Wang, Dongliang; Ma, Yanwei; et al.
Abstract: 122-type iron-based superconductors (IBS) have attracted extensive attention due to their excellent performance. The 100 m class Ba1− x K x Fe2 As2 (Ba-122) 7-filamentary IBS tapes were successfully fabricated by the Institute of Electrical Engineering, Chinese Academy of Sciences. In this study, we have performed tests of the 7-filamentary Ba-122 short tape samples (Bas samples) and the 100 m class 7-filamentary Ba-122 tape samples (Ba100 samples) under various kinds of strain using U-shaped bending spring devices. Both types of samples were still reversible even when the applied compressive strain reached −0.65%. In addition, the reversible tensile strain limit of the Bas and Ba100 samples were 0.25% and 0.28%, which increased to 0.38% and 0.41% after considering the effect of the cooling process.